Advances in Plant Ecophysiology Techniques (Springer International Publishing, 2018)
This handbook covers the most commonly used techniques for measuring plant response to biotic and abiotic stressing factors, including: in vitro and in vivo bioassays; the study of root morphology, photosynthesis (pigment content, net photosynthesis, respiration, fluorescence and thermoluminiscence) and water status; thermal imaging; the measurement of oxidative stress markers; flow cytometry for measuring cell cycle and other physiological parameters; the use of microscope techniques for studying plant microtubules; programmed-cell-death, and other parameters; last-generation techniques (metabolomics, proteomics, SAR/QSAR); hybridization methods; isotope techniques for plant and soil studies; and the measurement of detoxification pathways, volatiles, soil microorganisms, and computational biology. Every chapter is focused on the measurement of a parameter from a very practical point of view, including its use in plant ecophysiology and the meaning of the results that can be obtained.